MEMBUMIKAN FIQH ANTROPOSENTRIS: PARADIGMA BARU PENGEMBANGAN HUKUM ISLAM YANG PROGRESIF - Takdir, Mohammad (IAIN Tulungagung, 2019)
ABSTRACTThis study aims to explore the idea of anthropocentric fiqh as a new paradigm in the development of more equitable Islamic law for all people in the world. Nowadays, the study of fiqh growing in the community only centered on the binary decision between halal and haram which seemed to ignore the aspects of daily problem faced by the ummah. This study uses the anthropocentric paradigm as a criticism to the theocentric paradigm which focuses all problems of the ummah only to the God. The anthropocentric paradigm is a perspective on fiqh products which not only contain debates about the God's absolutes, but also concern on the human interests in obtaining justice and the benefits of every product of the ulama ijtihad. This study shows that anthropocentric fiqh is a model of the Islamic law development which is not oriented to the sacred text or the monopoly of interpretation of classical scholars. Anthropocentric Fiqh does not want to erase the legal provisions of the Shari'a as well as the results of the classical ulama's thoughts, but to strengthen the legal foundation which is in accordance to the needs of the ummah. So, anthropocentric fiqh is very compatible with the people situation who have their own problems related to the tradition or culture which are considered against the Islamic law.Keywords: Anthropocentric Fiqh, Tajdid, Islamic Law.